ANALISIS PENGARUH INLASI, KURS MATA UANG DAN SUKU BUNGA TERHADAP PERUBAHAN HARGA SAHAM PERUSAHAAN DI BURSA EFEK INDONESIA - Hamid Halin (Jurnal Ilmiah Ekonomi Global Masa Kini)
This research is purposed to know the influence of  inflation, rate of exchange and interest rate by simultan and parsial to change price share. This research population  at company which listed company of LQ45 in Indonesian Stock Exchange period 2009-2015.The collecting data’s techinuqe is used in this research by searching internet data in order to obtain secondary data and library research in order to obtain the fundamental theory which has support this research.  This research use model analyse doubled linear regresi with inflation, rate of exchange and interest rate as independent variable and change price share as dependen variable Result of research indicate that concurrently, share price change influenced by inflation, rate of exchange and interest rate. While pursuant to conducted research by using t test got by result of that inflation, rate of exchange and rate of interest not have an effect on to  change price shareKeyword : Inflation, rate of exchange and rate of interest, Price Change Share and  LQ45 Company.